Agronomic performance and genetic diversity among lines and soybean cultivars - Beliza Queiroz Vieira Machado; Ana Paula Oliveira Nogueira; Osvaldo Toshiyuki Hamawaki; Gabriel Lemes Jorge; Gabriel Fernandes Rezende; Jacqueline Siqueira Glasenapp; Raphael Lemes Hamawaki; Cristiane Divina Lemes Hamawaki (Bioscience Journal, 2017)
Knowledge of genetic diversity is of great importance to the contribution of plant breeding, as it helps plant breeders to better selecting parents for establishment of segregating populations. This knowledge is especially important to crops that presents a narrow genetic base as soybean. The objective of this work was to assess agronomic performance and genetic diversity of lines and soybean cultivars, in order to find those ones with potential to be used as parents in breeding programs. Experiment was carried out during 2015/2016 season in the Federal University of Uberlândia farm known as Capim Branco. A randomized complete block designed was applied in order to assess twenty-three morpho-agronomic features on twenty-four soybean genotypes. Significant genetic variability for all agronomic traits was found. Genotypes UFU B7, UFU B14, UFU B16, Msoy 6101 and UFUS 7910 were set as early maturity soybean, with life cycle duration ranging from 107.3 to 111 days. Genotypes UFU B1, UFU B3, UFU B8 and UFU B16 presented productivity values higher than national average of 2.870 kg ha-1. Genotypes were clustered by UPGMA, Tocher and canonical variables methods. Both UPGMA and Tocher methods formed four groups. NDF was the major contributor to genetic diversity. Hybridizations between UFU B3, UFU B8, UFU B16 genotypes with UFU B1 genotype might be promising for establishment of segregating populations shown superior genetic variability. Under these circumstances, it was concluded that agronomic features assessed were useful on detection of parents with potential to UFU's soybean breeding program.